Play and Learning in Early Childhood Settings International Perspectives - Pramling Samuelsson, Ingrid; Fleer, Marilyn (International Perspectives on Early Childhood Education and Development, 2009)
This book provides the first ever cultural-historical study of the play of children from birth to 2 years of age in their early childhood education and care settings across 7 countries. Researchers from New Zealand, Australia, Chile, Hong Kong China, Japan, Sweden and USA present their investigations of the play activities of infants and toddlers in their early childhood settings. They examine the cultural construction of play in these different contexts through a cultural-historical analysis. The book presents a review of the literature, drawing upon Vygotsky's (1966) work to frame the review, followed by a critique of research and theory on play within the field of early childhood education. It provides case examples of play within specific countries, mostly using Barbara Rogoff's (1998) 3 planes of analysis as a common approach for framing and analysing the data generated. It further examines how play has been enacted across countries and offers suggestions for future directions.